Socio-Economic Impact of Outbreak Cases Foot Mouth Disease (FMD) on Livestock Farmers - Merdekawati, Ihsani; Kurniawan, Meirli; Jamalurrusid, Achsan; Cahyaningati, Soby Eko (Journal of Posthumanism, 2025)
The re-outbreak of Food Mouth Disease (FMD) in cattle in Indonesia, including Probolinggo City, has caused several unavoidable impacts. One of them is the impact of socio-economic losses. This study aims to calculate the economic losses incurred due to the spread of FMD in cattle during the outbreak period with a focus on livestock farmers and also to find the social impact of FMD. This study used a quantitative calculation used to measure the total economic losses, and descriptive analysis based on the results of questionnaires to know the social impact and also quantitative calculations used to measure the total economic losses. The total economic loss reached USD 25,456. This loss appears as a loss arising from the death of beef cattle, the decrease in milk productivity of dairy cattle and the cost of controlling the spread of FMD in the form of treatment costs for infected cattle. In this location of study, it was found that the beef cattle were more affected than dairy cattle. Then, control costs arising not only from vaccination, but also from the provision of traditional medicine (herbs) and vitamins to restore the condition. For social impact, it was discovered that livestock farmers experienced stress and anxiety, which affected their relationships with their families.